Manajemen Ekstrakurikuler Pendidikan Anak Usia Dini (PAUD) dalam Meningkatkan Multiple Intelegensi - Eni Rakhmawati (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2019)
This research examines the management of extracurricular education early childhood. It is backed by that implementation of extracurricular activities on early childhood education face varieties of constraints in management. Therefore, extracurricular activities, early childhood education is supposed to be managed thoughtfully. The management of extracurricular activities are good and true will effect positively to the quality of early childhood education. The qualitative research methodology is library research. Method of data collection by collecting reference books the subject matter and book supporters. Data analysis techniques are content analysis. Results of the study show that the extracurricular management, early childhood education is implemented through the following four stages: (1) plan a needs analysis, types, background, goals, budget, materials, assessment tools, schedule, facilities and infrastructure, output criteria instructors, (2) organize the Division of duties, authority and responsibilities of the personnel of extracurricular activities, (3) carry out extracurricular activities appropriate planning and organizing, and (4) evaluate extracurricular activities.